Thin film synthesis of the organic-based magnet vanadium ethyl tricyanoethylenecarboxylate1. Issue 100 (29th October 2015) - Lu, Yu; Yu, Howard; Harberts, Megan; Epstein, Arthur J.; Johnston-Halperin, Ezekiel
<x xml:space="preserve">Abstract</x> We report the preparation and characterization of a new thin film organic-based magnet V[ETCEC]x, with TC of 161 ± 10 K, via low temperature chemical vapor deposition (CVD; T = 55 °C).